2020
DOI: 10.4103/njms.njms_49_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of crestal bone level in patients having low level of Vitamin D treated with dental implant with or without Vitamin D3 supplements

Abstract: Introduction: Vitamin D has been shown to play a vital role in bone mineral homeostasis by stimulating the intestinal absorption of calcium and phosphate. The critical role of Vitamin D in bone metabolism triggered the need to evaluate the effect of Vitamin D deficiency and hence replacement of the same on osseointegration of dental implants. This prospective study evaluated the crestal bone level in patients having low level of Vitamin D treated with dental implant with or without Vitamin D3 supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Zhou et al found an increase in osseointegration in osteoporotic rats given Vitamin D supplements (23), while Wu et al found an increase in the percentage of interaction of bone with implant in diabetic rats given Vitamin D supplements (23). According to the findings of this study, vitamin D stimulates osteoblasts and promotes the synthesis of extracellular matrix proteins by osteoblasts (24).…”
Section: Discussionsupporting
confidence: 54%
“…Zhou et al found an increase in osseointegration in osteoporotic rats given Vitamin D supplements (23), while Wu et al found an increase in the percentage of interaction of bone with implant in diabetic rats given Vitamin D supplements (23). According to the findings of this study, vitamin D stimulates osteoblasts and promotes the synthesis of extracellular matrix proteins by osteoblasts (24).…”
Section: Discussionsupporting
confidence: 54%
“…The articles excluded and the reasons for their exclusion are shown in Table 1 [ 24 , 25 , 26 , 27 , 28 ]. In this review, the study by Mangano et al [ 29 ] was considered a continuation of the study by Mangano et al [ 30 ], so it was treated as a single study for purposes of data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Higher vitamin D levels on the dental implant surgery day were associated with lower marginal bone loss after 6 and 12 months in the RCT from Kwiatek and co-workers [70]. Accordingly, on prospective clinical trial, there was a tendency for less peri-implant bone loss in patients taking vitamin D3 supplements [71]. Despite the limited number of studies, clinical findings support a potential role for supplementation in vitamin D deficient patients subjected to implant-based tooth replacement.…”
Section: Peri-implant Disease and Vitamin Dmentioning
confidence: 86%